Association of APOL1 Risk Alleles With Cardiovascular Disease in Blacks in the Million Veteran Program. Issue 12 (17th September 2019) - Bick, Alexander G.; Akwo, Elvis; Robinson-Cohen, Cassianne; Lee, Kyung; Lynch, Julie; Assimes, Themistocles L.; DuVall, Scott; Edwards, Todd; Fang, Huaying; Freiberg, S. Matthew; Giri, Ayush; Huffman, Jennifer E.; et al.
Abstract : Background: Approximately 13% of black individuals carry 2 copies of the apolipoprotein L1 ( APOL1 ) risk alleles G1 or G2, which are associated with 1.5- to 2.5-fold increased risk of chronic kidney disease. There have been conflicting reports as to whether an association exists between APOL1 risk alleles and cardiovascular disease (CVD) that is independent of the effects of APOL1 on kidney disease. We sought to test the association of APOL1 G1/G2 alleles with coronary artery disease, peripheral artery disease, and stroke among black individuals in the Million Veteran Program. Methods: We performed a time-to-event analysis of retrospective electronic health record data using Cox proportional hazard and competing-risks Fine and Gray subdistribution hazard models. The primary exposure was APOL1 risk allele status. The primary outcome was incident coronary artery disease among individuals without chronic kidney disease during the 12.5-year follow-up period. We separately analyzed the cross-sectional association of APOL1 risk allele status with lipid traits and 115 cardiovascular diseases using phenome-wide association. Results: Among 30 903 black Million Veteran Program participants, 3941 (13%) carried the 2 APOL1 risk allele high-risk genotype. Individuals with normal kidney function at baseline with 2 risk alleles had slightly higher risk of developing coronary artery disease compared with those with no risk alleles (hazard ratio, 1.11 [95% CI, 1.01–1.21]; P =0.039). Similarly, modest associations were identified with incident stroke (hazard ratio, 1.20 [95% CI, 1.05–1.36; P =0.007) and peripheral artery disease (hazard ratio, 1.15 [95% CI, 1.01–1.29l; P =0.031). When both cardiovascular and renal outcomes were modeled, APOL1 was strongly associated with incident renal disease, whereas no significant association with the CVD end points could be detected. Cardiovascular phenome-wide association analyses did not identify additional significant associations with CVD subsets. Conclusions: APOL1 risk variants display a modest association with CVD, and this association is likely mediated by the known APOL1 association with chronic kidney disease. Abstract : Supplemental Digital Content is available in the text.